Is cystatin C a good predictor of acute kidney injury after elective aortic surgery? - Maričić Prijić, Sanja; Uvelin, Arsen; Andjelić, Nada; Plećaš Djurić, Aleksandra; Popović, Radmila; Vicković, Sanja (Vojnosanitetski pregled, 2023)
Background/Aim. Acute kidney injury (AKI) is a frequent and serious complication after aortic surgery, which increases the length of hospital stay, costs, morbidity, and mortality. The aim of the study was to investigate the incidence of AKI and the most important preoperative and intraoperative predictive factors for AKI 72 hrs after elective infrarenal aortic surgery (IAS). Methods. This prospective observational study was performed at the Clinic of Anesthesia, Intensive Care and Pain Therapy, University Clinical Center of Vojvodina (UCCV), from October 2017 to April 2019. It included 140 adult patients who underwent an elective IAS. The occurrence of AKI was noted according to the Acute Kidney Injury Network (AKIN) criteria. A multivariate logistic regression model was used for potential predictive factors. Results. The incidence of AKI after the elective IAS at the Clinic of Anesthesia, Intensive Care and Pain Therapy, UCCV, was 28.56%. According to the receiver operating characteristic (ROC) curve analysis, the cut-off value of cystatin C serum concentration of 1.14 mg/L had the highest sensitivity (82.5%) and specificity (76%) in the differentiation of patients who will develop AKI. The final model contained the following variables: the presence of chronic kidney disease, the preoperative serum concentration of cystatin C > 1.14 mg/L, the application of colloid solutions in volume > 500 mL during the operation, and the total intravascular fluid replacement volume > 59 mL/kg in the intraoperative period. Conclusion. The incidence of AKI at the Clinic of Anesthesia, Intensive Care and Pain Therapy, UCCV, is somewhat higher compared to the literature data. A presurgical value of cystatin C above 1.14 mg/L is a good predictor of AKI after the elective IAS.
Keywords: aorta; cystatin c; elective surgical procedures; kidney failure, acute; prognosis; sensitivity and specificity.